2019
DOI: 10.3389/fvets.2019.00290
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Rabies Incidence and Its Geographic Spread in the Buffer Area Among Orally Vaccinated Wildlife in Ukraine From 2012 to 2016

Abstract: The statistics of rabies cases in Volyn, Lviv, and Zakarpattia oblasts of Ukraine from 2012 to 2016 were analyzed to establish spatial–temporal distribution of rabies endemic outbreaks and to identify causes of widespread infections among wild and domestic animals. The occurrence of rabies outbreaks in wild and domestic animals in Ukraine was also assessed to determine the effectiveness of oral rabies vaccination (ORV) efforts. According to our analysis, parenteral vaccination of domestic animals and ORV campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 14 publications
0
20
0
4
Order By: Relevance
“…In the United States, Canada, and Mexico, few cases were reported in cattle [53]. The same situation showing a very few reported rabies cases in cattle in Ukraine during 2012-2016 was reported [37].…”
Section: Epidemiologymentioning
confidence: 52%
See 2 more Smart Citations
“…In the United States, Canada, and Mexico, few cases were reported in cattle [53]. The same situation showing a very few reported rabies cases in cattle in Ukraine during 2012-2016 was reported [37].…”
Section: Epidemiologymentioning
confidence: 52%
“…In China, local rabies vaccines have been used for emergency immunization of beef and dairy cattle and Bactrian (two-humped) camels [8]. In Ukraine, vaccination of domestic dogs and cats, besides oral vaccination of wild animals, mainly foxes, is adopted to control rabies [37]. In Latin America, due to attacks of bats, rabies is a significant problem, especially in cattle; many countries tend to vaccinate cattle but with an inadequate response from owners.…”
Section: Prevention and Control Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Polupan et al (2019Polupan et al ( ) reported that in 2003Polupan et al ( , 2005Polupan et al ( , 2006Polupan et al ( , 2007Polupan et al ( , and 2008, over 2 000 rabies cases per year were recorded, 37% of which were found in foxes.…”
Section: Introductionmentioning
confidence: 99%
“…This contributed to a high number of rabies cases in dogs (over 19% of all rabies cases) and in cats (over 25% of all cases) in Ukraine. A particular problem was a large population of stray animals (Polupan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%